Herinnering, tradisie, teologie: Op weg na v49_n3_4_a1 verantwoordelike historiese hermeneutiek - Vosloo, RR (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
Memory, tradition, theology: en route to a responsible historical hermeneutics The 150 year anniversary of theological education at Stellenbosch in 2009 offers an opportunity to engage the question: How do we remember the past? This question points in the direction of the necessity for what one could call a responsible historical hermeneutic. This article highlights some contours for such a responsible historical hermeneutic, including the need to respect the continuity and discontinuity between us and the past; the need to embody an ethics of memory and history that will strengthen excluded voices; the need to take the interwovenness of our shared and dividing histories seriously; and the need to regain a dynamic understanding of tradition as counterpoint to forgetfulness.